Strategies and algorithms for the management of the difficult airway: Traditions and Paradigm Shifts 2017. (April 2017) - Schaeuble, Joerg C.; Heidegger, Thomas
Abstract: Several national guidelines for the management of the difficult airway have been updated since 2013. This article provides an overview on the most important changes in national difficult airway guidelines over the last four years. Recent recommendations and expert opinion regarding the management of the expected difficult airway, the unexpected difficult airway and emergency surgical airway access are addressed. Changes in obstetrical and paediatric airway guidelines, strategies for extubation of the difficult airway and prehospital airway management guidelines are pointed out. Highlights: Several national guidelines for the management of airway difficulties have been updated within the past four years. Beside tools and techniques, the importance of good planning, preparation and communication is emphasised. The need for education and training in airway management is strengthened. Essential changes were made in the recommendations for management of the obstetrical airway.